Robot-assisted vs laparoscopic pyeloplasty in children with uretero-pelvic junction obstruction (UPJO): technical considerations and results. Issue 6 (December 2019) - Esposito, Ciro; Masieri, Lorenzo; Castagnetti, Marco; Sforza, Simone; Farina, Alessandra; Cerulo, Mariapina; Cini, Chiara; Del Conte, Fulvia; Escolino, Maria
Summary: Background: Although both laparoscopic pyeloplasty (LP) and robot-assisted laparoscopic pyeloplasty (RALP) have reported excellent clinical outcomes, no evidence is currently available about the best surgical approach for surgical treatment of children with uretero-pelvic junction obstruction (UPJO). Objective: This study aimed to compare the outcomes of LP and RALP in children with UPJO. Study design: The medical records of all patients with UPJO, who underwent LP or RALP in three pediatric urology units over a 2-year period, were retrospectively reviewed. The authors excluded open pyeloplasty and cases with complex anatomy such as horseshoe kidney. A dismembered Anderson-Hynes pyeloplasty was performed in all cases. Results: Sixty-seven patients (39 boys and 28 girls) with a median age of 4 years (range 8 months–14 years) were included. Thirty-seven patients (55.2%) underwent RALP, and 30 patients (44.8%) underwent LP. Three patients of RALP group presented a recurrent UPJO. No significant difference was found in the median total operative time between RALP (133 min) and LP (139 min) ( P  = 0.33). The median anastomotic time was significantly shorter in RALP (79 min) compared with LP (105.5 min) ( P  = 0.001). Overall surgical success rate was 96.7% for LP and 100% for RALP ( P  = 0.78). As for postoperative complications, the authors recorded re-stenosis of UPJO in one LP patient (3.3%), who underwent redo-RALP. Discussion: According to the authors experience, robotic surgery should be indicated in patients older than 18–24 months with a body weight > 10–15 Kgs. Laparoscopic pyeloplasty requires advanced laparoscopic skills related to intracorporeal suturing. However, the learning curve of suturing in robotics is much shorter compared with laparoscopy. In fact, during LP, the authors have to place 2–3 transabdominal stay sutures to stabilize the uretero-pelvic junction, before performing the anastomosis. Conversely, the authors never needed to place stay sutures in RALP. Conclusions: The study experience suggested that RALP and LP give excellent results in children with UPJO. Laparoscopic pyeloplasty can be considered more minimally invasive than RALP because 3-mm trocars are adopted instead of 8-mm robotic ports. However, LP is technically challenging and has a bad ergonomics for the surgeon. Conversely, RALP is technically easier compared with LP, especially in redo procedures, with an excellent ergonomics. The main disadvantages of RALP remain high costs and size of robotic instruments. The choice to perform LP or RALP should be tailored to the individual case, considering patient's age and surgeon's experience.